Restorative Justice Alternative Criminal Case Settlement In Indonesia - Ridho Mamonto (Universitas Negeri Gorontalo, 2022)
This study aims to analyze the concept of resolving criminal acts in the Attorney General's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice, as well as to examine aspects of legal certainty in the Attorney General's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The type of research in writing this proposal is normative research, namely research that examines the study of documents such as legislation, court decisions, and legal theory. The approaches used by researchers in compiling this research are, among others: the Invitation Approach (Statue Approach). The results showed that in the Prosecutor's Regulation No. 15 of 2020, criminal cases can be closed by law and prosecuted based on Restorative Justice, except for recidivists. Prosecutor's Regulation No. 15 of 2020 lies in the guidelines that have been created and determined and are limited by requirements in their implementation.